1. Zapisz jak najkrócej i oblicz wartości wyrażeń .
a ) 5x+3y- 3x -2y , gdy x = 1 , y = 2
b ) 7z + 4c - z - 3c , gdy z = ²/₇ , c = ⅕
2.Rozwiąż równanie i sprawdź otrzymany wynik . L= ... P= ...
a) -5x + 4 = x- 8 b) - 2x - 7 = 2x - 7
c) -7x +5 = 11x +41 d) 36x - 14 = 14x - 36
e) 45x - 19 = 19x - 45 f ) 82x -9 = - 18x +1
g) 3x + 9 = - 3x + 9 h ) - 27x +1 = 2x +59
i) 7x - 13 =8 j) 3x - 4 = 4x

2

Odpowiedzi

2010-01-17T12:26:40+01:00
1.
a ) 5x+3y- 3x -2y = 2x +y = 2*1 + 2 = 4
b ) 7z + 4c - z - 3c = c + 6z = 2/7 + 6* 1/5 = 2/7 + 1,2 = 1 17/35
2.
a) -5x + 4 = x- 8
-6x = -12
x = 2
-5*2 + 4 = 2 - 8
-10 + 4 = -6
-6 = -6
b) - 2x - 7 = 2x - 7
-4x = 0
x = 0
-2*0 - 7 = 2*0 - 7
-7 = -7
c) -7x +5 = 11x + 41
-18x = 36
18x = -36
x = -2
-7*-2 + 5 = 11*-2 +41
14 + 5 = -22 +41
19 = 19
d) 36x - 14 = 14x - 36
22x = -22
x = -1
36*(-1) - 14 = 14*(-1) - 36
-36 - 14 = -14 - 36
-40 = -40
e) 45x - 19 = 19x - 45
26x = -26
x = -1
45*(-1) - 19 = 19*(-1) - 45
-64 = -64
f ) 82x -9 = - 18x +1
100x = 10
x = 0,1
82*0,1 - 9 = - 18 *0,1 +1
8,2 -9 = -1,8 +1
0,8 = 0,8
g) 3x + 9 = - 3x + 9
6x = 0
3*0 + 9 = -3*0 +9
9 = 9
h ) - 27x +1 = 2x +59
-29x = 58
29x = -58
x = -2
-27*(-2) +1 = 2*(-2) + 59
54 + 1 = -4 + 59
55 = 55
i) 7x - 13 =8
7x = 21
x = 3
7*3 - 13 = 8
21 - 13 = 8
8 = 8
j) 3x - 4 = 4x
-x = 4
x = -4
3*(-4) -4 = 4*(-4)
-12 - 4 = -16
-16 + -16
2010-01-17T13:34:57+01:00
1.
a)8x+5y
b)8z+7c

2.
a)-4x+4+8=16x
b)0x+14=14x
c)-4x+46=42x
d)50x-50=x
e)64x-64=x
f)100x-10=90x
g)6x+9+9h
h)-25x+60=-35x
i)7x-4=3x